Electroacupuncture for post-thoracotomy pain: A systematic review and meta-analysis. - Sohyeon Park; Yee Ran Lyu; So Jung Park; Min Seok Oh; In Chul Jung; Eun-Jung Lee (PLoS ONE, 2021)
Background Thoracotomy is an invasive surgical procedure that produces intense postoperative pain. Electroacupuncture has been used to induce analgesia in various situations, including after surgery. The aim of the following systematic review and meta-analysis was to evaluate the effect of electroacupuncture on post-thoracotomy pain. Methods The studies for the systematic review were searched using the following 9 databases: PubMed, Cochrane Library, EMBASE, MEDLINE Complete, Google Scholar, China National Knowledge Infrastructure (CNKI), Korean Medical Database (KMBASE), Koreanstudies Information Service System (KISS), and OASIS, without language restriction. Randomized controlled trials (RCTs) that met the inclusion criteria were selected. The quality assessment was performed using the Cochrane risk-of-bias tool, and RevMan 5.3 was used for meta-analysis. The review protocol is registered in the International Prospective Register of Systematic Reviews (PROSPERO) as CRD42019142157. Results Eleven randomized controlled trials were included in the systematic review. The meta-analysis was performed for two outcome measures: pain score 24 hours after surgery and total dose of opioid analgesics. A subgroup analysis was performed according to the control group: sham acupuncture and conventional analgesia group. Pain score 24 hours after surgery of electroacupuncture group showed a standard mean difference of -0.98 (95% CI: -1.62 to -0.35) compared to sham acupuncture. The standard mean difference was -0.94 (95% CI: -1.33 to -0.55) compared to conventional analgesia. The total dose of opioid analgesics of electroacupuncture group showed a standard mean difference values of -0.95 (95% CI: -1.42 to -0.47) compared to sham acupuncture. The standard mean difference was -1.96 (95% CI: -2.82 to -1.10) compared to conventional analgesia. Conclusion Current evidence suggests that electroacupuncture might provide useful pain relieving effect on post-thoracotomy patients. However, due to low quality and high heterogeneity of existing data, further rigorously designed studies should be performed to confirm the safety and efficacy.